2015
DOI: 10.1038/srep17421
|View full text |Cite
|
Sign up to set email alerts
|

Probing Origin of Binding Difference of inhibitors to MDM2 and MDMX by Polarizable Molecular Dynamics Simulation and QM/MM-GBSA Calculation

Abstract: Binding abilities of current inhibitors to MDMX are weaker than to MDM2. Polarizable molecular dynamics simulations (MD) followed by Quantum mechanics/molecular mechanics generalized Born surface area (QM//MM-GBSA) calculations were performed to investigate the binding difference of inhibitors to MDM2 and MDMX. The predicted binding free energies not only agree well with the experimental results, but also show that the decrease in van der Walls interactions of inhibitors with MDMX relative to MDM2 is a main fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 95 publications
2
32
0
Order By: Relevance
“…Mdm2 was mostly in an open state, while MdmX was mostly in a closed state [Figs. (b,c) and (c)], consistent with the original crystal structures and simulation studies …”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…Mdm2 was mostly in an open state, while MdmX was mostly in a closed state [Figs. (b,c) and (c)], consistent with the original crystal structures and simulation studies …”
Section: Resultssupporting
confidence: 84%
“…We also focused our attention on Y100/99 because of its well‐documented role in gating p53 binding. Previous computational studies suggested that the open conformation of Mdm2 increases the size of the pocket, allowing deeper p53 binding, while MdmX in the closed conformation causes a shallower binding pocket and pushes p53 “out”, reducing the binding affinity . It is also proposed that MdmX is closed due to residue differences between Mdm2 and MdmX .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Molecular dynamics (MD) simulations play an important role in successful exploration of protein-ligand interactions and conformational changes of proteins at the atomic level323334353637383940414243. Principal component (PC) analysis44454647, an important method of post-process analysis based on trajectories of MD simulations, shows a big potential in probing internal dynamics of protein motions4849.…”
mentioning
confidence: 99%